The Influence of the LIPIRTUP Strategy on the Short Story Writing Skills of Class VII Students at SMPN 24 Medan - Sinaga, Magdalena Shinta; Siregar, Rosdiana (Indonesian Journal of Advanced Research, 2023)
This research aims to determine the effect of the LIPIRTUP strategy on the short story writing skills of class VII students at SMPN 24 Medan. The method used in this research is the one-group pre-test post-test design experimental method. Hypothesis testing was carried out using the "t" test. The data obtained showed that students' skills in writing short stories before using the LIPIRTUP strategy were in the sufficient category with an average score of 65.90, while students' skills in writing short stories after using the LIPIRTUP strategy were in the moderate category. good with an average value of 73.45. Hypothesis testing shows tcount > ttable, namely 3.99470 > 1.69913, so the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there is an influence of the LIPIRTUP strategy on the short story writing skills of class VII students at SMPN 24 Medan.